Self‐Determination Theory and Word of Mouth about Energy‐Saving Behaviors: An Online Experiment. Issue 9 (September 2014) - Sweeney, Jillian C.; Webb, Dave; Mazzarol, Tim; Soutar, Geoffrey N.
ABSTRACT The growing community concern for the environment, and rising energy costs to consumers, has led many power utility companies to adopt strategies aimed at reducing energy consumption in the home and workplace. These strategies have typically been based on extrinsically regulated pricing mechanisms. Although more intrinsically driven interventions have been examined, they are often complex and expensive to implement due in part to the high level of human interaction involved. This two‐part study suggests simpler more cost‐efficient alternatives to enhancing energy saving. It does this via two separate but related studies that examined the application of self‐determination theory (SDT) and word of mouth (WOM) within online communities. The findings suggest a significant increase in reported energy‐saving behaviors over time supporting the role of SDT. There was also evidence that positive WOM increases satisfaction of the three psychological needs of autonomy, competence, and relatedness, further enhancing energy‐saving behavior. These findings have important implications for marketers in terms of behavior change.